2008
DOI: 10.3184/030823408x324670
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Aromatic Substitution of 7-f-butyl-1,3-dimethylpyrene: Preparation of 5-mono- and 5,9-di-substituted 7-f-butyl-1,3-dimethylpyrenes

Abstract: Formylation and acetylation of 7-t-butyl-1,3-dimethylpyrene selectively afforded the 5-mono-and 5,9-di-substitution products depending on the Lewis acid catalyst used, while bromination and nitration afforded the 6-substitution product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, the reaction conditions are hard to control and complex by‐products are formed. Although the t Bu groups can be preferably used to obtain the 1,3‐dibromopyrene selectively, electrophilic substitution of pyrene can occur at other positions, such as the 5‐ or 5,9‐positions, by formylation and acetylation 25. Furthermore, the use of two t Bu groups (i.e., at the 2‐ and 7‐positions) allows substitution at the 4‐, 5‐, 9‐, and 10‐positions of the pyrene molecule to occur 26.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reaction conditions are hard to control and complex by‐products are formed. Although the t Bu groups can be preferably used to obtain the 1,3‐dibromopyrene selectively, electrophilic substitution of pyrene can occur at other positions, such as the 5‐ or 5,9‐positions, by formylation and acetylation 25. Furthermore, the use of two t Bu groups (i.e., at the 2‐ and 7‐positions) allows substitution at the 4‐, 5‐, 9‐, and 10‐positions of the pyrene molecule to occur 26.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in our laboratory, we also reported the selective formation of the 5-mono-and 5,9-di-substitution products from 7-tert-butyl-1,3-dimethylpyrene by formylation and acetylation depending on the type of Lewis acid catalyst deployed. 12 More recently, the 1-and 3-positions of pyrene were brominated using 2-tert-butylpyrene; the tert-butyl group on the pyrene ring protects the ring from electrophilic attack at the 6,8-positions. applications.…”
mentioning
confidence: 99%
“…As showni nS cheme10, Kime ta l [40] showed that N,N-dimethylaniline and1 -(trifluoromethyl)benzene groups arer andomlyattachedatthe 1-,3 -, 6-,a nd 8-positionso fp yrenet hrough as tepwiseS onogashira coupling. [41] These results seem to indicatet hat the solvent and initiator used play as ignificant role in this bromination process. Thea bove examples inspired us to developanovels tereocontrolled method for thef unctionalization of pyrene in ordert oa ccessh igh-performance electroluminescencematerials.…”
Section: Bromination Of Pyrene 31 Regioselective Bromination Of Pyrenementioning
confidence: 80%
“…In addition, in the absence of initiator, bromination of compound 6 with NBS in carbon tetrachloride resulted in compounds 40 in 83 % yield and 41 in only 8 % yield. Similarly, in benzene, bromopyrene 41 was obtained in only 7 % yield along with recovered starting material (Scheme ) . These results seem to indicate that the solvent and initiator used play a significant role in this bromination process.…”
Section: Bromination Of Pyrenementioning
confidence: 91%
See 1 more Smart Citation